Functional Diversity and Ecosystem Services of Birds in Productive Landscapes of the Colombian Amazon - Jenniffer Tatiana Díaz-Cháux; Alexander Velasquez-Valencia; Alejandra Martínez-Salinas; Fernando Casanoves (Diversity)
The expansion of anthropogenic activities drives changes in the composition, structure, and spatial configuration of natural landscapes, influencing both the taxonomic and functional diversity of bird communities. This pattern is evident in the Colombian Amazon, where agricultural and livestock expansion has altered ecological dynamics, avifaunal assemblages, and the provision of regulating ecosystem services. This study analyzed the influence of agroforestry (cocoa-based agroforestry systems—SAFc) and silvopastoral systems (SSP) on the functional diversity of birds and their potential impact on ecosystem services in eight productive landscape mosaics within the Colombian Amazon. Each mosaic consisted of a 1 km2 grid, within which seven types of vegetation cover were classified, and seven landscape metrics were calculated. Bird communities were surveyed through visual observations and mist-net captures, during which functional traits were measured. Additionally, functional guilds were assigned to each species based on a literature review. Five multidimensional indices of functional diversity were computed, along with community-weighted means per guild. A total of 218 bird species were recorded across both land-use systems. Bird richness, abundance, and functional diversity—as well as the composition of functional guilds—varied according to vegetation cover. Functional diversity increased in mosaics containing closed vegetation patches with symmetrical configurations. Variations in functional guilds were linked to low functional redundancy, which may also lead to differences in the provision of regulating ecosystem services such as biological pest control and seed dispersal—both of which are critical for the regeneration and connectivity of productive rural landscapes. In conclusion, functional diversity contributes to the resilience of bird communities in landscapes with Amazonian agroforestry and silvopastoral systems, highlighting the need for landscape management that promotes structural heterogeneity to sustain regulating ecosystem services and ecological connectivity.